CAPACITY OF STRUCTURES ANALYSIS WITH INCREMENTAL DYNAMIC ANALYSIS & APPROXIMATE MODAL PUSHOVER ANALYSIS OF REINFORCED CONCRETE STRUCTURES - WIBOWO, FERRY
Incremental Dynamic Analysis (IDA) is an analysis developed to predict the seismic demand and the capacity of structures. The analysis requires nonlinear time history analysis of structures with incremental intensity of ground motions forming the entire range of structural responses.Because of IDA is a very complex time history analysis then an approximate method to analyse seismic demand of structures is developed namely Modal Pushover Analysis (MPA). MPA is implemented by improving the conventional push-over analysis (Capacity Spectrum Method) taking account for the contribution of higher modes of the structure under the seismic demand (Chopra & Goel 2002). In this study MPA has a good agreement with the response spectra analysis. Under MPA, the structural response under the seismic demand can be determined using Single Degree of Freedom (SDF) system for the nonlinear time history analysis. The results is then converted into roof displacement for each modes. The final result is the combination of each modes using SRSS under the same ground motion. Based on the study of 10, 15 and 20 stories of reinforced concrete structures both for open frame and dual system (portal and shearwall), it was found that MPA can be used as an alternative analysis other than IDA for Vb versus Uroof, with at least modes 2 and 3 should be included. The study of the response of the open frame showed that the MPA approximation isn't conservative/under-estimate as compared to IDA. However, the different between MPA and IDA in terms of the ratio of the roof displacement to the story height is less than 0.007. However, for the dual system, the response that the MPA approximation is very conservative/over-estimate as compared to IDA. But, for dual system the influence second and third mode are insignificant as the first mode was very dominant.